The non-antidepressant effects of citalopram: a clinician's perspective - Richter, Tomas; Paluch, Zoltan; Alusik, Stefan (Neuro endocrinology letters, 2014)
The authors present an overview of the most often discussed questions concerning citalopram, i.e. its proven effect on the QT interval and related dose reductions. They discuss citalopram's antiplatelet effect including the most recent data and draw attention to serotonin syndrome as its incidence is still underestimated. They go on to discuss hyponatremia pointing out that this condition may develop even in those taking low doses of citalopram. Finally, the authors provide a brief overview of the latest findings on osteoporosis and the serotonergic mechanism inducing it in individuals treated with a selective serotonin reuptake inhibitor.
Keywords: serotoninový syndrom; Serotonin Syndrome; citalopram; inhibitory agregace trombocytů; Osteoporosis; Citalopram; lidé; Serotonin Antagonists; Romanův-Wardův syndrom; Romano-Ward Syndrome; hyponatremie; osteoporóza; Platelet Aggregation Inhibitors; antagonisté serotoninu; Hyponatremia; Humans